A double Meckel's diverticulum in a 5-year-old girl - Ayman Alkhamisy; Ranim Kazzaz; Roaa Ghanem; Ahmad Amir Kayali; Mohamad Morjan (Elsevier, 2022)
Although Meckel's diverticulum (MD) is the most common congenital anomaly in the GI tract, it is usually located as one true diverticulum at the antimesenteric side of the small intestine. It is very rare to find MD as a double diverticulum. In literature, only four cases of a double MD were reported in pediatric population.A 5-year-old girl was brought to the emergency department complaining of periumbilical abdominal pain associated with frequent bilious vomiting. The only abnormal lab result was leukocytosis with neutrophilia. An erect abdominal X-ray revealed multiple air-fluid levels in the upper abdomen. On laparotomy, the intestinal loops were extensively dilated and adhesions were noticed. After releasing the adhesions, two different Meckel diverticula were surprisingly discovered, a small one located 15 cm from the ileocecal valve, and a large one causing the obstruction and located 35cm proximal to the ileocecal valve. A double diverticulectomy along with a primary repair was undertaken followed by an unremarkable postoperative course. Conclusion: Double MD is a rare and extraordinary entity that may be seen during the surgical practice, so it is crucial to trace the entire intestine during an exploratory laparotomy, especially the last 100 cm of the terminal ileum, to detect the associated congenital anomalies such as duplication or diverticula to avoid future mishaps.